Concomitant etoposide and cisplatin provided improved survival compared with docetaxel and cisplatin in patients with locally advanced non-small cell lung cancer treated with chemoradiotherapy. Issue 30 (July 2016) - Sen, Fatma; Tambas, Makbule; Ozkaya, Kubra; Guveli, Murat Emin; Ciftci, Rumeysa; Ozkan, Berker; Oral, Ethem Nezih; Saglam, Esra Kaytan; Saip, Pinar; Toker, Alper; Demir, Adalet; Firat, Pinar; et al.
Abstract : Abstract: Presently, there is no consensus regarding which chemotherapy regimen is best to administer with radiotherapy in patients with locally advanced non-small-cell lung cancer (LA-NSCLC). Herein, our aim was to compare the outcome of patients treated with either etoposide–cisplatin (EP) or docetaxel–cisplatin (DP) in this curative setting. Patients treated with either EP or DP and concurrent radiotherapy from 2004 to2012 were identified and their detailed medical records and follow-up information were obtained for analysis in this retrospective study. Survival rates were compared using Cox proportional hazards regression models with adjustments for confounding parameters provided by propensity score methods. A total of 105 patients were treated with concurrent chemoradiotherapy for LA-NSCLC (stage IIB-IIIA-IIIB). The median ages were 54 years (range, 32–70 years) and 55 years (range, 37–73 years) in the EP (n = 50) and DP (n = 55) groups, respectively. The median follow-up time was 27 months (range, 1–132 months) in the EP group and 19 months (range, 1–96 months) in DP group. There was no significant difference in baseline clinicopathologic features including age, sex, performance status, histologic subtype, and clinical TNM stages between groups. In the univariate analysis, the median overall survival of patients treated with EP was higher than that of patients treated with DP (41 vs. 20 months, P = 0.003). Multivariate analysis further revealed a survival advantage with EP compared with DP (hazard ratio [HR], 0.46; 95% confidence interval: 0.25–0.83; P = 0.009). The toxicity profile of the 2treatment groups was similar except that pulmonary toxicity was higher in the DP group (grade 3–4: 0% vs. 6%, P = 0.024). Concurrent chemoradiotherapy with EP may provide more favorable outcomes than DP and with an acceptable safety profile.